Chemical characterization of fruits of Garcinia brasiliensis Mart. - Caroline Woelffel Silva; Patricia Cristina Gonçalves; Camile Zanichelli Costa; Karla Lírio Soares; Patrícia Berilli Batista; Stephano Marques; Mário Roberto Maróstica Júnior; Stanislau Bogusz Junior; Oscar Núñez; Rodrigo Scherer (Ciência Rural)
ABSTRACT: The present study carried out a nutritional assessment of the pulp, peel, and seeds of fruits of bacupari (Garcinia brasiliensis). The proximate composition was carried out according to A.O.A.C. guide, organic acids by HPLC-PDA, minerals by ICP-OES, fatty acids by GC-FID, B-group vitamins, and the phenolic compounds profile by LC-MS/MS. Fresh fruit pulp has 12% carbohydrates, 2.8% fiber and low fat content. Furthermore, the fruits are also an important source of minerals such as manganese, zinc, and potassium. 15 fatty acids were identified with a higher portion of unsaturated fatty acids. Furthermore, the fruits are an excellent source of vitamin B1 (about 20% of the recommended daily intake), and of vitamin B12, a vitamin almost exclusively of animal origin, making the fruits interesting for people with dietary restrictions. The fruits also have the presence of bioactive compounds, such as phenolic acids and flavonoids, such as 4-hydroxybenzoic acid (1123 µg/100g), gallic acid (672 µg/100g), epicatechin (3907 µg/100g), and quercetin (658 µg/100g).